Effect of chromium and magnesium supplementation in broiler diets on body weight and some blood parameters - Kalaycioglu, L; Coskun, B; Kurtoglu, F; Kurtoglu, V (The Indian Journal of Animal Sciences, 2012)
The objective of the present study was to define the effect of supplementation of 20 mg/kg chromium (Cr) and 600 mg/kg magnesium (Mg), including two protein levels on Peterson x Avian chicks used in a 2 x 2 x 2 factorial design. The experiment lasted 51 days. Three different diets were fed between the days of 1-21, 21-35, and 35-51. Live weights and feed intake values were determined weekly. At the end of the experiment blood samples were drawn by cardiac puncture. Mg and albumin levels in serum were determined by using spectrophotometer and commercial test kits. In general, there were no statistically significant effects of Cr and/or Mg supplementation in broiler diets. But in low protein groups the supplementation of the minerals increased the growth performance parameters. High protein level diets unexpectedly reduced live weight gain and feed intake but feed conversion rates in high protein groups were better than the low protein groups. High level of protein increased serum albumin but decreased Mg levels. Mg supplementation increased serum Mg levels but not serum albumin levels while Cr supplementation did not cause any effect on levels of both parameters.